2020
DOI: 10.3892/mco.2020.2105
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of chemoradiotherapy with concurrent split‑dose cisplatin after induction chemotherapy with docetaxel/cisplatin/5‑fluorouracil for locally advanced head and neck cancer

Abstract: Chemoradiotherapy (CRT) with concurrent high-dose cisplatin (CDDP) is a standard treatment for locally advanced squamous cell carcinoma of the head and neck (LA-SCCHN). Docetaxel plus CDDP and 5-fluorouracil (TPF) induction chemotherapy (ICT) prior to CRT is considered for patients at high risk of distant metastases. The purpose of the current study was to evaluate the feasibility and efficacy of CRT with split-dose CDDP after TPF-ICT for LA-SCCHN. A total of 21 LA-SCCHN patients treated with TPF-ICT followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Anemia is one of the commonest complications in cisplatin chemotherapy [38] in both weekly and 3-weekly groups of patients in concurrent setting [37]. In our study, there was a greater fall of RBC count in weekly cisplatin group as compared to 3-weekly group.…”
Section: Red Cell Countsupporting
confidence: 46%
See 1 more Smart Citation
“…Anemia is one of the commonest complications in cisplatin chemotherapy [38] in both weekly and 3-weekly groups of patients in concurrent setting [37]. In our study, there was a greater fall of RBC count in weekly cisplatin group as compared to 3-weekly group.…”
Section: Red Cell Countsupporting
confidence: 46%
“…We observed thrombocytopenia in 14.8% cases, showing greater fall in the weekly group as compared to 3-weekly regimen with extremely significant statistical difference. Kogo M, et al [32] reported thrombocytopenia in 10.2% cases and Yokota T et al [38] reported in 85% cases receiving IC with docetaxel plus ciplatin and 5FU as combination chemotherapy. In another study, Chen JX et al [35] reported thrombocytopenia in both the groups (P < 0.05, P < 0.01) similar to studies by Furqan et al [37] and Karim et al [23].…”
Section: Platelet Countmentioning
confidence: 99%
“…No complaints or complications involving the tracheostomy were observed. The clinical trials that support the use of induction chemotherapy for hypopharyngeal cancer are not consistent as they have failed to exhibit a significant improvement and as a result, CCRT is used as a therapeutic option for a greater local and regional control ( 16 , 17 ).…”
Section: Case Reportmentioning
confidence: 99%
“…This tool can also be used in patients who receive primary surgical treatment for SCC, as a prognostic indicator of mortality and complications ( 21 ). Higher grading of pre-existent pathologies is associated with higher chances of severe acute toxicities, postoperative surgical complications and mortality rate ( 17 , 18 ). In the present study, ACE-27 indicated a moderate decompensation (grade 2) for cardiovascular system.…”
Section: Case Reportmentioning
confidence: 99%
“…Among all cancers, oropharyngeal squamous cell carcinoma (OPSCC) has one of the most rapidly rising incidences in high-income countries [ 3 , 4 ]. The American Joint Committee on Cancer (AJCC) differentiates OPSCC prognosis based on human papilloma virus (HPV) p16+ status [ 3 ], introducing a different staging category in the latest eighth edition of the AJCC TNM staging system [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. P16-related OPSCC is strongly associated with a favourable overall survival (OS) and disease-free survival rate (DSS), while, conversely, p16 negative OPSCC often flags a worse prognosis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%